Long-Term Protection After Primary Hepatitis B Vaccination: A Systematic Review - Hasniah, Hasniah; Perwitasari, Dyah Aryani; Supadmi, Woro (Sciences of Pharmacy, 2025)
Vaccination has proven effective in preventing HBV transmission and reducing related health burdens. This study aimed to systematically review the long-term effectiveness of the hepatitis B vaccine following primary vaccination. A literature search was conducted using PubMed, ProQuest, and the Cochrane Library following PRISMA guidelines. Keywords included "effectiveness," "hepatitis B," "HBV," "HepB," "vaccine," "vaccination," "immunization," "immune memory," "seroprotection," and "birth dose." Of 555 articles initially identified, nine met the inclusion criteria. Results showed that the duration of protection after primary vaccination ranges from 5 to 25 years, with an average seroprotection rate of 83.5%. Vaccination is vital for newborns, regardless of maternal HBV status, and healthcare professionals play a key role in promoting early immunization. Monitoring anti-HBs antibody levels is also recommended to assess the need for booster doses, which may help prevent HBV transmission and further reduce morbidity and mortality.